2015 IEEE Energy Conversion Congress and Exposition (ECCE) 2015
DOI: 10.1109/ecce.2015.7310596
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency MOSFET-based MMC for LVDC distribution systems

Abstract: Low-voltage DC (LVDC) systems offer a promising means for improving distribution system efficiency and reliability. The DC-AC conversion stage, however, is one of the main challenges for LVDC networks. A low-voltage modular multilevel converter (MMC) for LVDC distribution systems is proposed in this paper. Analysis is presented to show that its efficiency can exceed that of a conventional 2-level converter. The low voltage rating of each MMC submodule enables MOSFETs to be used in place of IGBTs to reduce powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 13 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…They can be achieved by MMCs made with silicon carbide metal-oxide semiconductor field-effect transistor (SiC MOSFET) and Si MOSFET [50]. The use of MOSFET instead of IGBT is able to reduce switching losses, while the use of synchronous rectification reduces conduction losses [51]. In [52], an MMC has been used as an interface with the power grid of a Smart Home that includes photovoltaic generation, energy storage, and recharging of electric vehicle, all connected to a DC bus.…”
Section: Low Voltage Multi-level Invertermentioning
confidence: 99%
“…They can be achieved by MMCs made with silicon carbide metal-oxide semiconductor field-effect transistor (SiC MOSFET) and Si MOSFET [50]. The use of MOSFET instead of IGBT is able to reduce switching losses, while the use of synchronous rectification reduces conduction losses [51]. In [52], an MMC has been used as an interface with the power grid of a Smart Home that includes photovoltaic generation, energy storage, and recharging of electric vehicle, all connected to a DC bus.…”
Section: Low Voltage Multi-level Invertermentioning
confidence: 99%
“…1. Previous investigation of the Si MOSFET MMC [11][12][13][14] has shown that conduction losses dominate switching loss due to low effective cell switching frequency. One phase leg of a 3-phase 5-level Si MOSFET MMC converter is shown in Fig.…”
Section: Ac/dc Converters For Ev Chargingmentioning
confidence: 99%
“…The prevalence of conduction losses in MMC makes parallel connection of MOSFETs attractive in order to reduce on-state resistance and hence reduce conduction loss. However, previous studies [11][12][13][14] did not include measured switching losses as Si MOSFET parallel connection was increased, so measured Si MOSFET switching losses will be explored in this paper. In addition, the possibility of reducing EMI using slowed switching was proposed [11], with modelled losses suggesting that switching could be considerably slowed without impacting overall converter loss.…”
Section: Ac/dc Converters For Ev Chargingmentioning
confidence: 99%
See 2 more Smart Citations